Tecnologias digitais da informação e comunicação e a alfabetização de nativos digitais - Araújo, Eliane Oliveira Santos (Universidade Federal do Tocantins, 2021)
This paper analyzes the possibilities of integrating ICT into the curriculum of literacy classes, from the perspective of teachers of the public schools of Palmas, Tocantins, aiming to explain the training needs of these literacy teachers. It is well known that the development of digital technologies has caused significant changes in educational practices. They are increasingly present in daily school life and teachers need to qualify to deal with these tools, which can innovate in teaching and learning. The universe of research is composed of teachers and literacy teachers and the management team of the Palmas, Tocantins municipal education network, in a total of three school units and approximately 60 teachers. All were invited to participate in the research, but the adhesion was voluntary. Thus, the research had 39 participants. This is a qualitative research, which values the description and explanation of the investigated phenomena. Data collection was performed from online questionnaire and document analysis. The results showed that there is a need for structuring technological and digital resources in the researched schools, as well as evidencing the relevance of continuing education and / or training in the context of ICTs, for teachers, for the educational use of such technologies. Therefore, as a contribution of the present research, a plan for continuing teacher education was developed, appropriate to the context.